1976
DOI: 10.1515/zna-1976-1204
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variations of Spontaneous Magnetization in a Layered Ising Model

Abstract: The extrema of the position-dependent spontaneous magnetization in a periodically layered twodimensional Ising model are calculated exactly. Their asymptotic behaviour for infinite width of the surrounding homogeneous sublayer is given. The perturbations caused by the neighbouring sublayers on this extremum in a very thick sublayer are shown to be decoupled. Thus the asymptotic decay of the magnetization far from a single layer-shaped inhomogeneity can be inferred from the quoted asymptotics of an extremum, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Consequently, the generating function in ( 26) becomes (22), reproducing the 2-d behavior again as it should. More generally there is a crossover for finite m: If α is expressed in terms of t ∝ T /T c − 1 as in [11], then α −j is exponentially small when m|t| is large, and the system behaves as two-dimensional, otherwise it acts one-dimensional.…”
Section: Limiting Casesmentioning
confidence: 59%
See 1 more Smart Citation
“…Consequently, the generating function in ( 26) becomes (22), reproducing the 2-d behavior again as it should. More generally there is a crossover for finite m: If α is expressed in terms of t ∝ T /T c − 1 as in [11], then α −j is exponentially small when m|t| is large, and the system behaves as two-dimensional, otherwise it acts one-dimensional.…”
Section: Limiting Casesmentioning
confidence: 59%
“…As m increases, one needs to calculate more and more roots. We have shown that in the limit m → ∞, the generating function becomes the well-known square-root function (22) for the correlation function of Onsager's 2-d Ising model. Therefore, it would be very difficult, but most interesting, to study the scaling behavior of these correlations in the limit, m → ∞ and T → T c , where T c is Onsager's critical temperature given by (1).…”
Section: Correlation Function Of a Single Strip Of Finite Widthmentioning
confidence: 96%